IT-Enabled Broadcasting in Social Media: An Empirical Study of Artists’ Activities and Music Sales - Chen, Hailiang; De, Prabuddha; Hu, Yu Jeffrey (Information Systems Research, 2015)
With the emergence of social media and Web 2.0, broadcasting in the online environment has evolved into a new form of marketing due to the much broader reach enabled by information technology. This paper quantifies the effect of artists’ broadcasting activities on a well-known social media site for music, MySpace, on music sales. We employ a panel vector autoregression model to investigate the interrelationship between broadcasting promotions in social media and music sales, while controlling for influential factors such as advertising in traditional media channels, album prices, new music releases, user-generated content, and artist popularity. We characterize two types of broadcast messages in the MySpace context, personal and automated. We find that broadcasting in social media has a significant effect on sales even after controlling for the aforementioned factors, and more important, the effect mainly comes from personal messages rather than automated messages. We also show that the timing and content of personal messages play a role in affecting sales. Our findings point to the importance of conducting captivating conversations with customers in social media marketing.